A UHF RFID system with on-chip-antenna tag for short range communication. (May 2015) - Peng, Qi; Zhang, Chun; Zhao, Xijin; Wang, Zhihua
Abstract A UHF RF identification system based on the 0.18 μm CMOS process has been developed for short range and harsh size requirement applications, which is composed of a fully integrated tag and a special reader. The whole tag chip with the antenna takes up an area of 0.36 mm2, which is smaller than other reported tags with an on-chip antenna (OCA) using the standard CMOS process. A self-defined protocol is proposed to reduce the power consumption, and minimize the size of the tag. The specialized SOC reader system consists of the RF transceiver, digital baseband, MCU and host interface. Its power consumption is about 500 mW. Measurement results show that the system's reading range is 2 mm with 20 dBm reader output power. With an inductive antenna printed on a paper substrate around the OCA tag, the reading range can be extended from several centimeters to meters, depending on the shape and size of the inductive antenna.